2016
DOI: 10.1007/s00449-016-1623-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different chemical pretreatments of elephant grass (Pennisetum purpureum, Schum.) used as a substrate for cellulase and xylanase production in submerged cultivation

Abstract: This study evaluated the potential use of elephant grass biomass, a highly productive species, for cellulase and xylanase production by the cellulolytic mutant Penicillium echinulatum 9A02S1 in submerged cultivation, using untreated biomass, biomass pretreated with different concentrations of NaOH, H2SO4 or NH4OH, or biomass pretreated with H2O at 121 °C. For filter paper activity, all cultivation carried out with pretreated elephant grass under the evaluated conditions showed superior activity when compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…These pretreatment methods decrease the cellulose crystallinity and the degree of polymerization as well as increase the specific surface area (Sanchez and Cardona, 2008). Menegol et al (2016) also revealed that physical pretreatment leads to higher ethanol production after delignification of elephant grass. However, studies demonstrated that more reduction of biomass particles i.e.…”
Section: Biomass Size Reductionmentioning
confidence: 95%
“…These pretreatment methods decrease the cellulose crystallinity and the degree of polymerization as well as increase the specific surface area (Sanchez and Cardona, 2008). Menegol et al (2016) also revealed that physical pretreatment leads to higher ethanol production after delignification of elephant grass. However, studies demonstrated that more reduction of biomass particles i.e.…”
Section: Biomass Size Reductionmentioning
confidence: 95%
“…The recalcitrant structure of lignocellulosic biomass is the main constraint of its bioconversion [13,14,15,16,17,18]. Varied pretreatment strategies such as chemical methods (e.g., acid, bases, salts and solvents), physico-chemical processes (e.g., steam explosion, liquid hot water (LHW) and ammonia fiber expansion (AFEX) and biological methods have been developed in attempts to remove hemicellulose and/or lignin from lignocellulosic wastes and reduce the crystallinity of cellulose [13,19,20,21,22,23,24]. It is widely accepted that efficient pretreatment should avoid the use of expensive chemicals, improve fiber reactivity and maximize the recovery/formation of fermentable sugars, avoid formation of enzyme inhibitory byproducts, preserve cellulose and hemicellulose fractions that are easily accessible to hydrolysis enzymes and minimize energy requirements [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, corrosion problems and sugar degradation are less severe in alkaline processes than in acid pretreatment. Alkaline pretreatment is also effective in delignifying the biomass [7,20,22,24]. A mild alkali concentration (<4% w/w ) favors enzymatic hydrolysis especially for low-lignin materials [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioconversion process is still constrained due to the recalcitrance of these energy crops. Different pretreatment strategies such as pretreatments using acid, alkaline or hot water, explosion pretreatments with steam or ammonia, and biological pretreatment have been reported for reducing the recalcitrance of lignocellulosic biomass wastes, and hence, enhancing the digestibility of these biomass wastes [12][13][14][15][16][17][18]. Chemical pretreatment has been extensively investigated, from lab-scale studies to large-scale ethanol fermentation applications, especially those using low lignin biomass (e.g., agricultural wastes) as substrates [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%